Can raising instructional time crowd out student pro-social behaviour? Evidence from Germany - Christian Krekel (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We study whether raising instructional time can crowd out student pro-social behaviour. To this end, we exploit a large educational reform in Germany that has raised weekly instructional time for high school students by 12.5% as a quasi-natural experiment. We find that this rise has a negative and sizeable effect on volunteering, both at the intensive and at the extensive margin. It also affects political interest. There is no similar crowding out of scholastic involvement, but no substitution either. We conclude that instructional time plays an important role in shaping student pro-social behaviour.
Keywords: I21; I28; D01; 330; Instructional Time; Student Pro-Social Behaviour; Volunteering; Scholastic Involvement; Political Interest; Quasi-Natural Experiment; "G8" Reform; SOEP